ANTI-INFLAMMATORY ACTIVITY OF PLATYCODIN D ON ALCOHOL-INDUCED FATTY LIVER RATS VIA TLR4-MYD88-NF- - Wu, Jing-tao; Yang, Gui-wen; Qi, Cui-hua; Zhou, Lei; Hu, Jian-guo; Wang, Mao-shan (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The current study was designed to evaluate the effect of PD, triterpenoid saponins extracted from the roots of Platycodon grandiflorumon on alcohol-induced fatty liver and investigate the possible mechanism of anti-inflammation and anti-endotoxin. Methods and Materials: A rat model was set up by feeding alcohol and fish oil to experimental animals, which then were treated with PD of 10, 20, 30 mg/kg body weight/day for 4 weeks, respectively. Whereafter, liver function enzymes, endotoxin of serum and liver lipid were assayed by biochemical methods, cytokines, histochemistry of hepatic tissue, the protein expression of CD14 and the TLR4, the mRNA expression of MD-2, MyD 88 and TRAF-6 were assayed. Results: Treatment with PD on ALF rats significantly decreased the levels of ALT, AST and TBIL, coefficient of liver index and the hepatic tissue contents of TG, additionally and dramatically ameliorated gut leakiness, decreased serum endotoxins levels, down-regulated MD-2 and CD14 levels, as well as the mRNA expression of TLR4, MyD88 and TRAF-6, accordingly suppressed NF-